Inactivation of Pseudovirus Expressing the D614G Spike Protein Mutation using Nitric Oxide‐Plasma Activated Water - Paritosh Patel; Neha Kaushik; Tirtha Raj Acharya; Sudakshya S. Lenka; Soujanya Ghosh; Rizwan Wahab; Suresh K. Verma; Eun Ha Choi; Nagendra Kumar Kaushik (Advanced Science)
Abstract Variants of concern (VOCs) of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) exhibit high infectivity due to mutations, particularly in the spike protein, that facilitate enhanced binding of virus to human angiotensin‐converting enzyme 2 (hACE2). The D614G mutation, situated in S1‐domain, promotes the open conformation of spike protein, augmenting its interaction with hACE2. Activated water neutralizes pathogens by damaging biological molecules; however, its effect on mutated SARS‐CoV‐2 or VOCs requires further exploration. Here, the efficacy of nitric oxide (NOx)‐plasma activated water (PAW) in inhibiting infections by SARS‐CoV‐2 pseudovirus expressing D614G‐mutated spike protein is investigated, which serves as a model for mutated SARS‐CoV‐2. Results demonstrated high prevalence of D614G mutation in SARS‐CoV‐2 and its VOCs. NOx‐PAW is non‐toxic to cells at high concentration, inhibiting infection by 71%. Moreover, NOx‐PAW induced structural changes in S1‐domain of spike protein, reducing its binding affinity and lowering clathrin‐mediated endocytosis‐related gene expression. Additionally, in silico analysis revealed NOx species in NOx‐PAW played key role in impairing S1‐domain function of the mutated SARS‐CoV‐2 pseudovirus by interacting directly with it. Collectively, these findings reveal the potent inactivation ability of PAW against mutated SARS‐CoV‐2 and suggest its potential application in combating emerging variants of SARS‐CoV‐2 and other viral threats.